FARMER PREFERENCES ON QUALITY AND YIELD CHARACTERISTIC OF NEW PADDY VARIETIES IN DONGGALA DISTRICT - Heni S.P. Rahayu (Widyariset, 2012)
New improved variety is a component of technology that hold an important role in increasing rice production. Farmers preferences of improved varieties have to be known because it affects on the level of farmer adoption of new paddy varieties. The aims of this research are to understand the characteristics of paddy that are important to farmers and to know the most prefered new varieties in Donggala. The research is a participatory research which supported by site observation. The data were analyzed by perceived quality method. The results show that the characteristics that are important to farmers preference in Donggala are production, pest and disease rate, the number of tillers, rice texture, the ease of harvest, the age of harvest, plant height and panicle length. However the paddy variety which is most favored by the farmers in Donggala is Inpari 4.